Second primary melanoma: incidence rate and risk factors. (19th May 2020) - Villani, A.; Fabbrocini, G.; Costa, C.; Greco, V.; Scalvenzi, M.
Abstract : Linked article : N. Pastor‐Tomás, et al. J Eur Acad Dermatol Venereol 2020; 34 : 2295–2302. https://doi.org/10.1111/jdv.16341